Printing with mechanically interlocked extrudates using a custom bi-extruder for fused deposition modelling. Issue 6 (18th July 2018) - Khondoker, Mohammad Abu Hasan; Asad, Asad; Sameoto, Dan
Abstract : Purpose: This paper aims to target to print functionally gradient materials (FGM) devices made of immiscible polymers in multi-material fused deposition modelling (FDM) systems. The design is intended to improve adhesion of dissimilar thermoplastics without the need for chemical compatibilization so that filaments from many different sources can be used effectively. Therefore, there is a need to invent an alternative solution for printing multiple immiscible polymers in an FDM system with the desired adhesion. Design/methodology/approach: In this study, the authors have developed a bi-extruder for FDM systems which can print two thermoplastics through a single nozzle with a static intermixer to enhance bonding between input materials. The system can also change the composition of extrudates continuously. Findings: The uniqueness of this extruder is in its easy access to the internal channel so that a static intermixer can be inserted, enabling deposition of mechanically interlocked extrudates composed of two immiscible polymers. Without this intermixer, the bi-extruder extrudes with simple side-by-side co-extrusion having no mechanical interlocking. The bi-extruder was characterized by printing objects using pairs of materials including polylactic acid, acrylonitrile butadiene styrene and high impact polystyrene. Microscope images of the cross-sections of the extrudates confirm the ability of this bi-extruder to control the composition as desired. It was also found that the mechanically interlocked extrudates composed of two immiscible polymers substantially reduces adhesion failures within and between filaments. Originality/value: In this study, the first-ever FDM extruder with a mechanical blending feature next to the nozzle has been designed and used to successfully print FGM objects with improved mechanical properties.